A Blockchain-Oriented Framework for Cloud-Assisted System to Countermeasure Phishing for Establishing Secure Smart City. (21st April 2023) - Kumar, Narendra; Goel, Vikas; Ranjan, Raju; Altuwairiqi, Majid; Alyami, Hashem; Asakipaam, Simon Atuah
Abstract : The information that is saved in the cloud about users is protected by a number of different safeguards in order to facilitate the development of smart cities. Phishing and other forms of social engineering are two examples of misleading tactics that may be used by hostile actors to get sensitive information about users. Phishing is still the first step of a multistage assault, despite the significant technological advancements that have been made to it in recent years. Phishing kits have evolved to become attack tools that are much simpler, more user-friendly, and more readily available as time has gone. Indicators of a successful phishing assault include using foreign characters in the URL, typosquatting of prominent domain names, reserved characters in redirections, and multichain phishing. When papers with these types of phishing URLs are uploaded to cloud storage, hackers get a helping push in the right direction. The use of cloud servers in the commission of these assaults is becoming more common. The currently available software to disallow list phishing URLs does not provide sufficient protection against multilevel phishing and instead places the onus of safety on the user to protect themselves. In addition, the immutability of blockchain data and the avalanche effect both demonstrate their effectiveness as crucial safety measures. In view of the recent advances in technology, we suggest an implementation of filtering that is based on blockchain technology to safeguard the cloud-based data of users. The Phish Block that has been presented is able to recognize homographic phishing URLs with an accuracy of 91 percent, thus ensuring the security of cloud storage.